2010
DOI: 10.1177/1479164109360269
|View full text |Cite
|
Sign up to set email alerts
|

The synthetic GLP-I receptor agonist, exenatide, reduces intimal hyperplasia in insulin resistant rats

Abstract: We studied the effect of a synthetic GLP-1 receptor agonist, exenatide, a drug approved for the treatment of type 2 diabetes, on the recovery from vascular injury in Zucker (non-diabetic) fatty rats. Exenatide 5.0 microg/kg per day or saline was administered for seven days before, and 21 days after balloon catheter mediated carotid injury. A pair feeding experiment helped differentiate between the drug itself and the known effects of the drug on decreased food intake. Body weight and glucose (weekly), carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…In many studies, cardiovascular diseases such as hypertension, atherosclerosis, and heart failure have been shown to be associated with abnormal vascular remodeling following vascular damage to the fundamental interactions between endothelial cells and VSMCs. This damage occurs via excess ROS production in the vasculature that modulates migration, adhesion, contractility, proliferation and hypertrophy, angiogenesis, apoptosis, and aging [5,35]. The anti-proliferative and anti-migratory effects of gemigliptin in our study are similar to the findings of Lim et al [38].…”
Section: The Beneficial Effects Of Gemigliptinsupporting
confidence: 92%
See 1 more Smart Citation
“…In many studies, cardiovascular diseases such as hypertension, atherosclerosis, and heart failure have been shown to be associated with abnormal vascular remodeling following vascular damage to the fundamental interactions between endothelial cells and VSMCs. This damage occurs via excess ROS production in the vasculature that modulates migration, adhesion, contractility, proliferation and hypertrophy, angiogenesis, apoptosis, and aging [5,35]. The anti-proliferative and anti-migratory effects of gemigliptin in our study are similar to the findings of Lim et al [38].…”
Section: The Beneficial Effects Of Gemigliptinsupporting
confidence: 92%
“…Moreover, GLP-1 can regulate hepatic glucose output, glucagon release, gastric emptying, insulin secretion, and appetite, leading to body weight loss [3,4]. Exendin-4, a GLP-1 agonist, attenuates intimal hyperplasia by balloon injury in the type 2 diabetic rat model [5] and exerts a cardioprotective effect in ischemia-reperfusion injury [6] and chronic heart failure [7], consistent with a 20% cardiovascular risk reduction in type 2 diabetic patients [8]. Likewise, DPP-4 inhibitors such as sitagliptin and anagliptin prevent atherosclerosis in apo E-deficient mice by improving endothelial dysfunction and suppressing the inflammatory response [9][10][11].…”
Section: General Characteristics Of Dipeptidyl Peptidase-4 (Dpp-4) Inmentioning
confidence: 99%
“…Taken together, these findings suggest that upon receptor binding by exendin-4, PKA is activated, which leads downstream to an increased activity of eNOS and subsequent NO production in SMCs, which suppress the proliferation of these cells [38]. On the other hand, another publication recently proposed that eNOS is not involved in the reduction of the intimal hyperplasia with exendin-4 treatment [15]. However, the authors only studied the expression of eNOS levels, which was slightly but not significantly increased, in lysates from the aortic arch and did not look at the activation of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that human coronary artery endothelial cells express GLP-1R and that both native GLP-1 (7-36) and exendin-4 are able to activate the receptor, leading to increased endothelial cell proliferation and decreased apoptosis [13,14]. GLP-1R is expressed on SMCs and treatment with exendin-4 has previously been shown to decrease neointima formation in a mouse model of vascular injury as well as in insulin-resistant rats [15,16]. However, how this effect impacts adjacent endothelial cells or the injured vessel wall, or what molecular pathways are involved has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Given that rats predominantly feed during the dark cycle, it is not necessary to administer a second dose of the peptide for the reduction of food intake as would be necessary if using the drug for glycemic control. Additionally, dosages needed to produce a sustained weight loss were based on previous studies and were significantly higher in rats than in humans [26,44,45,46,47,48]. …”
Section: Discussionmentioning
confidence: 99%